A Case Study of Mirambika: a Child-friendly Approach to Pre-school Education - KAUSHAL, SAVITA (THE PRIMARY TEACHER, 2014)
To foster child centric and joyful learning and provide an enabling environment we have to make our ‘schools ready’. It is not just about making ‘a school’ child friendly– it is about a transformation of the system with child-centred planning, focusing on overall development of children. A school that is ready for children will accept all children, with sensitivity to cultural diversity. It would provide opportunity for enhancement of potential of each individual child. It would ensure smooth and seamless transition for the child from home to ECCE centre to formal education. Such a school will form effective relations with parents and community. In the present study the author has tried to understand the pedagogic/philosophic significance of Mirambika— the reason for its existence; its innovations and experiments especially from the point of view of pre-school education